Properties of free and microencapsulated quercetin: A literature review - Frez, Fábio Luiz Vieira; Querubin, Beatriz Estorine; Rampani, Edicleia Martins; Teixeira, Flávia; Maschio, Igor Maluf Duarte; Rocha, Larissa Crozatti; Sério, Maria Eduarda; Lima, Thiago Kenzo Guinoza; Oliveira, Victória Hoffmann De; Frez, Flávia Cristina Vieira (Seven Editora, 2024)
Quercetin is a bioactive compound classified as a polyphenolic flavonoid found in several plant sources, known for its antioxidant and anti-inflammatory properties, being able to modulate the expression of pro-inflammatory cytokines and transcription factors associated with inflammation. This is a literature review, with a search in scientific journals to provide a view of the therapeutic benefits of quercetin, especially for individuals with chronic diseases, in addition to presenting an innovative formulation such as microencapsulation, as an alternative to the free quercetin already used in supplementation, enabling the reduction of daily doses with considerably similar results. In the findings, it is highlighted that supplementation with bioactive compounds present in human food can significantly benefit individuals who have frailties, in addition, starting the discussion about pharmacological formulations that can reduce dosage and improve the site of absorption of these micronutrients, will make adherence to supplementation more effective, the importance of trained professionals for prescription with scientific basis and interest in Always keep up-to-date. Future research may add even more subsidies that corroborate the findings of this work. DOI:https://doi.org/10.56238/sevened2023.007-024